Pengaruh Pemberian Kombinasi Pakan Pelet Dan Pakan Alami Terhadap Pertumbuhan Benih Ikan Gabus (Channa striata) - Agus Juliantara; Dewa Gede Semara Edi; I Made Kawan (Fakultas Pertanian, Universitas Warmadewa, 2020)
Snakehead fish (Channa striata) is a freshwater fishery commodity in Indonesia which has a high protein content. Many studies on the benefits of snakehead fish have resulted in an increase in the amount of demand for these fish. One of the production factors that support fish farming is feed. The snakehead fish seeds have an average length of 2 cm, with rudimentary digestive organs. Therefore, the most suitable feed as seed feed is natural food. Commonly used natural feed is water fleas (Daphnia sp.) and silk worms (Tubifex sp.). This study aims to determine the effect of a combination of feed on the growth of snakehead fish seeds and to determine the combination of feed that gives the highest growth in snakehead fish seeds. This research was conducted at the Fisheries Resources Development Laboratory, Warmadewa University for 60 days, from March to April 2020. The method used in this study was an experimental study using a completely randomized design (CRD) with six treatments and three replications. The analysis used in this study was Analysis of Variance (ANOVA), and continued with the Least Significant Difference (LSD) test. The results showed that there was an effect of combination feeding on the growth of snakehead fish as indicated by the increase in absolute weight and length. And the sixth treatment is a combination of feed that provides the highest growth in snakehead fish seeds.